Chapter 4 Business cycle in croatia: by the dynamic synchronization technique (2019)
The theme of turning points dating and research into the synchronisation of business cycles, co-movements of the two cycles by the method of indexes and calculation of correlation coefficients in the manner the authors conducted in this study on the case of Croatia, is a widely exploited research field in the modern analysis of business cycles. Methodologically, our study leans on the research program of concordance index calculations by the authors hereafter. Various aspects of economic complexity today in Croatia deal with different but dependent economic parts such as, for example: the tourism, labour, monetary and production ingredients which will be presented and examined in this paper. It should also be noted that understanding of the cyclical characteristics in Croatia's economic activities in a systematic way could be important for the purposes of planning, coordination and resource allocation in the sustainable economic development of Croatia. This paper applies the nonparametric procedure to estimate the concordance index for the assumed variable, and to study its cyclical features in relation to the reference variable. Our working assumption, broadly speaking, is that the findings should lead us to some important stylized facts about business cycle dynamics in Croatia. The motivation for researching the main problem in this paper, i.e. researching the synchronization quality of business cycles in Croatia in comparison with the EU industrial cycle, lies in the authors’ professional curiosity to penetrate into the secrets of the current deep recession, which is turning into an economic depression, which, certainly, drags the “cumulative causality” from earlier times. The novelty of this paper is that it will reveal the strength of synchronization of specific segments of economic life, both within Croatia and in relation to the EU economic fluctuations. The presumed contribution of this paper is reflected in the identification of the economic reality segments, which crucially contributes to the decline in economic activity in Croatia.